Problem prawdy w koncepcji społeczeństwa otwartego Karla R. Poppera - Woźniak, Kamil (Humaniora. Czasopismo Internetowe, 2025)
The aim of this paper is to establish the status of truth in Karl Popper’s concept of the open society. This political philosopher explicitly dealt with the meaning of truth in politics, so the hermeneutic method was used, according to which the researcher reconstructs and analyses the questions and answers contained in the author’s reasoning. According to the main hypothesis, Popper uses a weak definition of truth in his conception of an open society. For this purpose, the concept of truth as a regulative idea is analysed, including the role of critical rationalism in the open society. The relevance of a weak definition of truth in social partial engineering is discussed, as well as the contemporary challenges of post-truth.